The transcriptome response of astronaut leukocytes to long missions aboard the International Space Station reveals immune modulation - Stratis, Daniel; Trudel, Guy; Rocheleau, Lynda; Pelchat, Martin; Laneuville, Odette (Frontiers in Immunology, 2023)
Introduction: Spaceflight leads to the deconditioning of multiple body systems including the immune system. We sought to characterize the molecular mechanisms involved by capturing changes in leukocyte transcriptomes from astronauts transitioning to and from long-duration spaceflight. Methods: Fourteen male and female astronauts with ~6-month long missions aboard the International Space Station (ISS) had ten blood samples collected throughout the three phases of the study: one pre-flight (PF), four in-flight (IF) while onboard the ISS, and five upon return to Earth (R). We measured gene expression through RNA sequencing of leukocytes, applied generalized linear modelling to assess differential expression across all ten time-points followed by the analysis of selected time-points, and functional enrichment of changing genes to identify shifts in biological processes. Results: Our temporal analysis identified 276 differentially expressed transcripts grouped into 2 clusters (C) showing opposite profiles of expression with transitions to and from spaceflight: C1 decrease-then-increase, and C2 increase-then-decrease. Both clusters converged towards average expression between ~2 and ~6 months in space. Further analysis of spaceflight transitions identified the decrease-then-increase pattern with most changes: 112 down-regulated genes between pre-flight and early spaceflight; and 135 up-regulated genes between late in-flight and return to Earth. Interestingly, 100 genes were both down-regulated when reaching space and up-regulated landing on Earth. Functional enrichment at the transition to space related to immune suppression, increased cell housekeeping functions and reduced cell proliferation. In contrast, egress to Earth related to immune reactivation. Conclusion: The leukocytes’ transcriptome changes describe rapid adaptations in response to entering space followed by opposite changes upon returning to Earth. These results shed light on immune modulation in space and highlight the major adaptive changes in cellular activity engaged to adapt to extreme environments.